HUBUNGAN PENGETAHUAN TENTANG ASI DENGAN PERILAKU IBU SAAT MENYUSUI DI KABUPATEN BANTUL - Merta Kusuma, Reni; Ariningtyas, Ristiana (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Breastmilk is essential for baby’s growth and development as well as for maternal health. Basic Health Research has reported that exclusive breastmilk coverage in Indonesia has only reached 42% in 2012. In Special Regency of Yogyakarta, the coverage was fluctuative along the years of 2008 to 2012. There has been a decrease in exclusive breastmilk coverage that leads to a need to conduct some interventions. The interventions are required in order to prevent lower nutritional status in babies. Methods: This research was a retrospective research, with cross sectional approach. This research employed survey to test the relationship between knowledge and mothers’ attitude during breastfeeding. Results: Research showed the relationship between knowledge and mothers’ attitude during breastfeeding had the score of r=0,104 and p=0,14, which meant that there was not a significant relationship between knowledge and mothers’ attitude during breastfeeding Conclusion: There was not a significant relationship between knowledge and mothers’ attitude during breastfeeding Keywords: Knowledge, breastfeeding, breastmilk